Generating and testing ecological hypotheses at the pondscape with environmental DNA metabarcoding: A case study on a threatened amphibian. Issue 2 (28th November 2019) - Harper, Lynsey R.; Lawson Handley, Lori; Hahn, Christoph; Boonham, Neil; Rees, Helen C.; Lewis, Erin; Adams, Ian P.; Brotherton, Peter; Phillips, Susanna; Hänfling, Bernd
Abstract: Background: Environmental DNA (eDNA) metabarcoding is revolutionizing biodiversity monitoring, but has unrealized potential for ecological hypothesis generation and testing. Aims: Here, we validate this potential in a large‐scale analysis of vertebrate community data generated by eDNA metabarcoding of 532 UK ponds. Materials & Methods: We test biotic associations between the threatened great crested newt ( Triturus cristatus ) and other vertebrates as well as abiotic factors influencing T. cristatus detection at the pondscape. Furthermore, we test the status of T. cristatus as an umbrella species for pond conservation by assessing whether vertebrate species richness is greater in ponds with T. cristatus and higher T. cristatus Habitat Suitability Index (HSI) scores. Results: Triturus cristatus detection was positively correlated with amphibian and waterfowl species richness. Specifically, T. cristatus was positively associated with smooth newt ( Lissotriton vulgaris ), common coot ( Fulica atra ), and common moorhen ( Gallinula chloropus ), but negatively associated with common toad ( Bufo bufo ). Triturus cristatus detection did not significantly decrease as fish species richness increased, but negative associations with common carp ( Cyprinus carpio ), three‐spined stickleback ( Gasterosteus aculeatus ), and ninespine stickleback ( Pungitius pungitius ) were identified. Triturus cristatus detection was negatively correlated with mammal species richness, and T. cristatus was negatively associated with gray squirrel ( Sciurus carolinensis ). Triturus cristatus detection was negatively correlated with larger pond area, presence of inflow, and higher percentage of shading, but positively correlated with HSI score, supporting its application to T. cristatus survey. Vertebrate species richness was significantly higher in T. cristatus ponds and broadly increased as T. cristatus HSI scores increased. Discussion: We reaffirm reported associations (e.g., T. cristatus preference for smaller ponds) but also provide novel insights, including a negative effect of pond inflow on T. cristatus . Conclusion: Our findings demonstrate the prospects of eDNA metabarcoding for ecological hypothesis generation and testing at landscape scale, and dramatic enhancement of freshwater conservation, management, monitoring, and research. Abstract : We evaluated eDNA metabarcoding as a tool for ecological hypothesis generation and testing using Triturus cristatus as a case study. We found that many factors previously reported to influence T. cristatus detection were reinforced by eDNA metabarcoding and patterns previously observed at local scale can also be observed at the pondscape. We identified individual species associations between T. cristatus and other vertebrates, reaffirming those previously established using conventional methods and providing new support for associations reported anecdotally by herpetofauna workers. We found vertebrate species richness was higher in ponds containing T. cristatus, which suggests T. cristatus conservation may confer protection to other aquatic and terrestrial biodiversity.